John C. Lowber, Ordinances of the Corporation of the City of Philadelphia, at 15-16, Ordinance No. 3, § 4 (1812) - (:unkn) unknown (My University, 1721)
That if any person or persons, of what sex, age, degree or quality soever, from and after publication hereof, shall fire any gun or other fire-arms, or shall make, or cause to be made, or sell or utter, or offer to expose to sale, any squibs, rockets or other fire works, or shall cast, throw or fire, any squibs, rockets, or other fire works, within the city of Philadelphia, without the governor's special license for the same, of which license due notice shall first be given to the mayor of the said city, such person or persons so offending, and being thereof convicted before any one justice of the peace of the said city, either by confession of the party so offending, or by the view of any of the said justices, or by the oath or affirmation of one or more witnesses, shall for every such offence forfeit and pay the sum of five shillings
Keywords: DISCHARGE